Способ количественного определения йода методом инверсионной вольтамперометрии - Дерябина В. И. Валентина Ивановна; Слепченко Г. Б. Галина Борисовна; Фам Кам Ньунг; Кириллова М. Е. Марина Евгеньевна
опубл. 20.08.12